Maurizio Balistreri, "Sex robot. L’amore al tempo delle macchine" - Umbrello, Steven (Filosofia, 2020)
A new book by Maurizio Balistreri, Sex robot. L’amore al tempo delle macchine, is reviewed. Sex robots not only exacerbate social, ethical and cultural issues that already exist, but also come with emergent and novel ones. This book is intended to build on the recent research on both robotics and the growing scholarship on sex robots more generally, however with greater attention to the developments of the philosophical issues of how to deal with these new artefacts and steps for living among these types of systems into the future.